2012
DOI: 10.1007/s00216-012-5921-y
|View full text |Cite
|
Sign up to set email alerts
|

Au:CdHgTe quantum dots for in vivo tumor-targeted multispectral fluorescence imaging

Abstract: Near-infrared gold-doped CdHgTe quantum dots (QDs) with improved photoluminescence and biocompatibility were developed using an aqueous solution route with L-glutathione and L-cysteine as stabilizers. As-prepared Au:CdHgTe QDs were covalently linked to arginine-glycine-aspartic acid (RGD) peptide, anti-epidermal growth factor receptor (EGFR) monoclonal antibody (MAb), and anti- carcinoembryonic antigen-related cell adhesion molecule-1 (CEACAM1) MAb separately. Three Au:CdHgTe QD bioconjugates (QD800-RGD, QD820… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Detailed histological examination of the tumor tissue revealed that targeting was vascular integrin α V β 3 specific with little extravasation. Over the last several years, many studies from other research groups have also demonstrated that RGD peptide-conjugated QDs could exhibit highly specific tumor targeting and reduced accumulation in the lung, kidney, and heart in mice models [86, 137-140]. …”
Section: In Vivo Targeted Imaging With Qdsmentioning
confidence: 99%
“…Detailed histological examination of the tumor tissue revealed that targeting was vascular integrin α V β 3 specific with little extravasation. Over the last several years, many studies from other research groups have also demonstrated that RGD peptide-conjugated QDs could exhibit highly specific tumor targeting and reduced accumulation in the lung, kidney, and heart in mice models [86, 137-140]. …”
Section: In Vivo Targeted Imaging With Qdsmentioning
confidence: 99%
“…Regarding CEA expression [136], specific probes were developed to detect in vivo this oncofetal protein, by labeling specific monoclonal antibodies with Cy5.5 [137], Alexafluor488 [138], fluorescent cyanine DY-676 [139], QD820 [140], or bioluminescent proteins such as Renilla Luciferase [141] and Gaussia Luciferase [142]. Even if Renilla and Gaussia Luciferases are not fluorescent probes, this is an alternative strategy that can be used to target CEA by Optical imaging using Bioluminescence.…”
Section: Tumor Cell Biomarkersmentioning
confidence: 99%
“…Cetuximab (or Erbitux, a monoclonal antibody already used in cancer therapy) has been labeled with Cy5.5 [154–156], QD840 [140] or Bodipy-FL [157] (a fluorophore that emits at 513 nm). Cy5.5-Cetuximab [156] has been injected in mice bearing MCF-7 and MDA-MB-231 breast cancers, and the tumor localization was monitored by fluorescence imaging.…”
Section: Tumor Cell Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…10 So far, many near-infrared range (NIR) fluorescent probes have been developed (such as quantum dots) for in-vivo imaging studies. [11][12][13][14][15] A single-view two-dimensional (2-D) imaging system is the mainstream of in-vivo fluorescence imaging equipment. [16][17][18][19] However, they cannot meet the needs for accurate positioning during the studies.…”
Section: Introductionmentioning
confidence: 99%